Urinary urobilinogen trtre as a bedside screening test for malaria fever - Mufti, W.S.; Renuka, K.G.D.; Somesan, P.K.; Sheriff, M.H.R.; Dharmadasa, K. (My University, 1987)
With the present interest in malaria throughout the country an earlier diagnosis of malaria would ease overcrowding in medical Wards. A study was conducted at the University Medical Unit to assess the urinary urobilinogen titre test as an early bedside screening test for malaria. Blood film examination for malaria parasite in comparison requires more expertise and a microscope. Similar studies have been reported by Khan et al. Patients presenting with fever and chills/rigors, where there was no other obvious pathology were admitted to the study. 20 patients were studied over a period of 2 months (November- December '86). Till 21.12.86. Urinary Urobilinogen Titre test was done using Ehrlichs' Aldehyde Reagent, on neat urine and on urine, diluted by 1/10.1/20,1/30..1/200,1/300 etc. Time interval between urine sample collection and the last chill/rigor was also neated. Results: Preliminary results are presented in the table below. Total number of patients- 20, Malaria patients- 06, Patients with other fevers- 11, Sex - all males, Age range - 19-62yrs, Mean age -34.1yrs, Mean Urobilinogen titre of malara patients - 76.7, Mean urobilinogan titre of patients with other fevers - 23.5, Average time taken for blood film report - 40 hrs. Average time taken for urinary urobilinogen report - 3hrs. Malaria patients- Dilution of urinary urobilinogen >1/30 -95%, Patients with other fevers- Dilution of urinary urobilinogen<1/30 - 95% We concluded that the 1. Urinaryurobilinogen titre test is useful bedside test for ealy screening of malaria. 2. A titre of>1/30 on admission of patient makes the diagnosis of malaria likely and may be used as an important deciding factor to commence treatment.